Pengaruh Penghargaan Intrinsik dan Penghargaan Ekstrinsik Terhadap Kinerja Karyawan dengan Perilaku Kerja Inovatif sebagai Variabel Intervening: Studi Pada Karyawan KSPPS BMT An Najah Pekalongan - Alfina Zulfa Brilianti; Edy Raharja (Diponegoro Journal of Management, 2025)
This study aims to analyse the effect of intrinsic reward and extrinsic reward on employee performance, with innovative work behaviour as an intervening variable, in employees of KSPPS BMT An Najah Pekalongan. Specifically, this study examines how both types of rewards affect employee performance and whether innovative work behavior plays a role in the relationship.This study uses a quantitative method with a Structural Equation Modeling (SEM) approach. Data were collected through questionnaires distributed to 76 respondents who were KSPPS BMT An Najah Pekalongan employees. Data analysis used the Smart Partial Least Square (Smart-PLS) application version 4.The results of the study indicate that (1) Intrinsic Reward have a positive and significant effect on Employee Performance; (2) Extrinsic Reward also have a positive and significant effect on Employee Performance; (3) Intrinsic Reward have a positive and significant effect on Innovative Work Behavior; (4) Extrinsic Reward have a negative and insignificant effect on Innovative Work Behavior; and (5) Innovative Work Behavior does not have a significant effect on Employee Performance.